Formulation and evaluation of transdermal delivery system of an anti-hypertensive drug - Goswami, D. S.; Uppal, N. (Creative Pharma Assent, 2013)
The present study was aims to formulate and evaluate transdermal drug delivery for sustained release of an anti-hypertensive drug Captopril, it is considered as drug of choice in anti hypertensive therapy and is reported for potential administration through transdermal route. The investigation was carried out to study the effect of different proportion of ethyl cellulose and PVP a hydrophobic and hydrophilic polymer respectively. Transdermal patches were prepared using different combination of the two polymers by solvent evaporation technique. Polyvinyl alcohol was used to prepare the backing membrane and dibutyl phthalate as a plasticizer. Several Physicochemical parameter like moisture content, moisture loss, thickness, film folding endurance, tensile strength, flatness were studied. For all the formulations, in vitro drug release was studied using modified diffusion cell. Formulations with highest proportion of polyvinyl pyrolidone shows faster release whereas increasing proportion of ethyl cellulose produces a prolonged regimen of sustained drug delivery through transdermal route for a period of 24 hrs.